Assessing Allele Frequencies of Single Nucleotide Polymorphisms in DNA Pools by PyrosequencingTM Technology - Jon Wasson; Gary Skolnick; Latisha Love-Gregory; M. Alan Permutt (BioTechniques)
Single nucleotide polymorphism (SNP) association studies searching for differences in allele frequencies between cases and controls have been widely used for genetic analysis. Individual genotyping is prohibitively expensive in large sample sizes. Pooling of samples provides the obvious advantage of higher throughput and lower cost. Here we report our results with the analysis of SNP allele frequencies in DNA pools using PyrosequencingTM technology. For seven different SNPs, we observed a mean difference of 1.1 ± 0.6% between allele frequencies determined in two different DNA pools (n = 150 cases and 150 controls) compared to individually genotyped samples.